From Sustainable Development to Ecologically Sustainable Development: A Reappraisal of Section 24(b)(iii) of the Constitution of South Africa, 1996 - Chikuruwo, Rufaro (South African Yearbook of International Law)
This paper offers a conceptual analysis of ecologically sustainable development in contrast to sustainable development. The analysis focuses on ecologically sustainable development as encapsulated in section 24(b)(iii) of the Constitution of the Republic of South Africa, 1996. The paper argues that ecologically sustainable development denotes preserving earth’s ecological systems. The paper further argues that ecologically sustainable development, as contained in section 24(b)(iii) of the Constitution, requires a shift from the ambiguous concept of sustainable development to ecologically sustainable development. The paper highlights the importance of prioritising environmental concerns when considering economic or social development. In essence, the study emphasises that ecologically sustainable development, as embedded in section 24(b)(iii), seeks to sustain the environment and not development activities. The paper concludes that ecologically sustainable development is a vehicle for facilitating the necessary paradigm shift required for better environmental protection as per section 24(b)(iii).